Influence of Packaging Design, Promotion and Brand Image on Consumer Buying Interest (Study Case of Consumers Glek-Glek Tea Nganjuk) - Ratna Ningtyas Nur Romadhona; I Nyoman Sudapet; Hamzah Denny Subagio (LPPM NAROTAMA UNIVERSITY, Indonesia, 2018)
This study aims to determine the effect of packaging design, promotion and brand image on consumer buying interest in NganjukGlek-Glek Tea. The population used in this study were consumers of Glek-Glek Tea Nganjuk with 100 respondents. The data analysis method used is multiple linear regression analysis. The results of the analysis show that simultaneously the packaging design, promotion and brand image variables have a significant effect on consumer buying interest, this is evidenced by the significance value of 0,000 or less than 0.05 and F 127,634> ft. 1.98. The results of the analysis partially indicate that the variable promotion of significance value 0.002 <0.05, which means that it has a significant effect on buying interest and brand image significance value 0,000 <0.50 which means that it significantly influences buying interest, while packaging design variables partially significance value 0.542.> 0.50 which means does not significantly influence buying interest.